'Five years ago I was on suicide watch…now I'm in college gaining a qualification'. Issue 6 (2nd July 2020) - Buchanan, Denise Rosemary
ABSTRACT: In the United Kingdom, although one in four adults reportedly experienced mental health difficulties within a one-year period, only 25% of them received treatment for their condition. Moreover, this group of adults are underrepresented in full-time employment and education and so to discover ways which may help to counteract this imbalance, an interpretive narrative study involving 15 adults with mental health problems was carried out. All the participants had attended classes in a Further Education college and were asked about their recent experiences of learning; their narratives were analysed in relation to well-being and transformative learning theory. Although certain negative aspects of their learning were identified which had the potential to impede their sense of well-being and potential transformative learning, these were outweighed by the numerous benefits that were reported. Nevertheless, the findings revealed that unless certain wider societal factors were sufficiently addressed, and specific support from the college Mental Health Advisers was provided, the potential for these benefits to be fully realised was hindered. This article argues that facilitating further education opportunities for adults with mental health problems may assist in promoting their wellbeing and a pathway to a different future, if the recommendations of this article are implemented.